(3JGQjN YKeGf Hf SYjO GdOGQei Yf jMji Hf eYjf aj JQLjM GdQhGI hJYOjdges ((3eMeO Hf CHj YHO Gddg Hf LHQjd GdCfUGQi s)
(3ChdgG (B:s
(3GUMGH GdRgQi CNHQfG CHh jMji RcQjG Hf CMeO GdHdNi aQCg GdOGQei bdJ dg eYeQ CMH Gdjc ai GdRgQi Ch edc abGd edc s
(3BNQgG (B:s
(3ef HGH ef jYQa HGdcfi (B) (3hSCdJg Yf CHj fYGeI GdSYOi abGd (B: (3KbI Je cJGH GdJGQjN (B) s
(3GdfGSN eGdc ddfSNIs
(3HBNQgG bQGAI Ydi CHj RcQjG jMji Hf CMeO Hf fYeI GdebOSi hbQGAI CNQi HOeTb SfI (B730s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs